2020
DOI: 10.3389/fgene.2020.559478
|View full text |Cite
|
Sign up to set email alerts
|

H3K4me3-Mediated Upregulation of LncRNA-HEIPP in Preeclampsia Placenta Affects Invasion of Trophoblast Cells

Abstract: Preeclampsia (PE) is a pregnancy-related disease defined as onset of hypertension and proteinuria after the 20th week of pregnancy, which causes most maternal and perinatal morbidity and mortality. Although placental dysfunction is considered as the main cause of PE, the exact pathogenesis of PE is not yet fully understood. Long non-coding RNAs (lncRNAs) are implicated in a broad range of physiological and pathological processes, including the occurrence of PE. In this study, we investigated the expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…However, many genes with deregulated expression were not associated with DNA methylation raising the possibility of altered chromatin signatures leading to abnormal gene expression in this placental disorder (Leavey et al, 2018). Indeed, upregulated expression of LncRNA by increased H3K4me3 has been observed in preeclampsia placentas (Sun et al, 2020), and the levels of H3K4me3 as detected by immunocytochemistry are decreased (Meister et al, 2021). Until now the connection between sperm chromatin and placenta function has been unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…However, many genes with deregulated expression were not associated with DNA methylation raising the possibility of altered chromatin signatures leading to abnormal gene expression in this placental disorder (Leavey et al, 2018). Indeed, upregulated expression of LncRNA by increased H3K4me3 has been observed in preeclampsia placentas (Sun et al, 2020), and the levels of H3K4me3 as detected by immunocytochemistry are decreased (Meister et al, 2021). Until now the connection between sperm chromatin and placenta function has been unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Successful placental and foetal development during the progression of pregnancy require adequate invasion of extravillous trophoblast cells into the uterine, and impaired trophoblastic invasion and spiral artery remodelling are widely considered as hallmarks of PE 3,4 . According to the literature, reduced trophoblastic invasion and spiral artery remodelling may be due to abnormal trophoblast differentiation, migration, angiogenesis and apoptosis, which may cause reduced uteroplacental perfusion and trigger hypoxia and inflammatory responses in the placenta, and may finally result in the occurrence of PE 5–10 . Besides, a variety of other potential molecular mechanisms have been suggested, including oxidative stress, endoplasmic stress, altered NK cell signalling and others 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer cells, EZH2 expression can be targeted by miR‐101 upon hypoxia‐inducible factor 1α/β (HIF‐1α/β) induction 29 . HIF is a transcription factor protected from degradation in various cells under hypoxic conditions and plays an essential role in modulating responses to hypoxia by controlling the expression of multiple genes 10,30 . HIF‐1α is stabilized when the concentrations of oxygen are below the specific critical oxygen threshold thus accumulating in the hypoxic cell, and HIF‐1β is constitutively present in the cell nucleus 31 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al have confirmed that some lncRNAs may participate in the pathogenesis of preeclampsia through methylation and signaling pathways [14]. Sun et al also studied the effect of the lncRNA-HEIPP expression on the pathogenesis of preeclampsia [15]. These findings suggested that lncRNA may play a role in hypertensive disorders in pregnancy.…”
Section: Introductionmentioning
confidence: 94%